Perinatal results according to delivery route in macrosomic newborns treated at the National Maternal-Perinatal Institute January - December 2019 - Ramos-Miranda, Karen Lissette (2022)
Introduction: Through the years, macrosomia in newborns has been linked to a high rate of maternal-perinatal morbidity and mortality, being double compared to non-macrosomic newborns, there is an increase in birth weight over the years. In the INMP in 2016, 8.7% of all deliveries were macrosomic, which is why the study is addressed. Objective: To determine the perinatal results according to the method of delivery in macrosomic newborns treated at the National Maternal-Perinatal Institute in the period January - December 2019. Materials and Methods: Comparative, retrospective, cross-sectional descriptive study, with a census sample of 430 medical records. The variables: perinatal results (Apgar, need for hospitalization, complications, newborn's weight) and method of delivery (vaginal delivery, elective cesarean section, emergency cesarean section with the opportunity of vaginal delivery until the last resort). The technique was document review and previously validated and reliable data collection sheet instruments. Descriptive statistics were used in the analysis. Results: In elective cesarean section, there were no cases of brachial plexus paralysis, clavicle fracture, hospitalization in the NEO ICU, or Apgar less than 7 points at 5 minutes, if 20% (32 of 167) of Respiratory Distress Syndrome (SDR), 17% (27 of76) hypoglycemia; RDS 54% (100 of 167), clavicle fracture 27% (50 of 62), brachial plexus palsy 16% (30 of 47) was greater vaginally, newborns from cesarean sections with the opportunity of vaginal delivery, 14% presented clavicle fracture, 41% RDS, 25% hypoglycemia, 20% brachial plexus palsy. The worst perinatal results were with more than 4500 grams and vaginally. Conclusions: The results according to the method of delivery were better in elective cesarean sections compared to vaginal deliveries and emergency cesarean sections with the opportunity of vaginal delivery, being necessary an adequate assessment and prevention from the prenatal stage.